The effect of 8 weeks of Strenuous Endurance Training on Heme oxygenase-1 and TNF-α in Gastrocnemius and Soleus muscle Tissue of male Wistar rats - Aghaali Ghasemnian; Zahra Ghorbanlou; akram karimiasl Asl; Jabar Seifpanahi Shabani (Mazandaran University of Medical Sciences, 2020)
Background and Objectives: Oxidative stress from exercise, either injured muscles and reduces performance in athletes, or stimulates the production of cytokines from many cells. body respond to oxidative stress by activating antioxidant defenses and other protective devices to counteract these body pressures. Therefore, the purpose of this study is to investigate the effect of 8  weeks of strenuous endurance training on HO-1 and TNF-α  in gastrocnemius and soleus muscle tissue of male wistar rats. Material and Methods: 16 adult male Wistar rats, were randomly divided in 2 groups (control and endurance training). The strenuous endurance training protocol included running on the treadmill for 8 weeks (5 sessions per week). Standard meal and water were freely provided for the subjects. 24 hours after the last session of training and 4 hours of overnight fasting,  tissue samples were collected and HO-1 and TNF-α levels were measured by ELISA method. Independent t-test was used for data analysis. Results: The results showed that 8 weeks of strenuous endurance training did not have a significant effect on the amount of HO-1 enzyme in gastrocnemius and soleus muscle (P˃0/05). Also, 8 weeks of strenuous endurance training had no significant effect on TNF-α in soleus and gastrocnemius muscle (P˃0/05). Discussion and conclusion: Due to the lack of effect of exercise on the levels of HO-1 and TNF-α, it can be said with caution that regular exercise has created a useful adaptation.